2011
DOI: 10.1136/heartjnl-2011-300178
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of Doppler echocardiographic coronary flow reserve in the left anterior descending artery

Abstract: CFR on LAD provides useful information for vessel stenosis and prognostic assessment in both hypertensive and normotensive patients. However, diagnostic specificity is reduced in hypertensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 50 publications
1
38
0
5
Order By: Relevance
“…Transthoracic echocardiography–derived CFR of the LAD has shown excellent concordance with invasive Doppler flow wire22 and optimal reproducibility 34. Of note, by using this methodology, we sample pulsed Doppler‐derived velocities in the distal LAD, which represent good correlates of coronary microvascular function (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Transthoracic echocardiography–derived CFR of the LAD has shown excellent concordance with invasive Doppler flow wire22 and optimal reproducibility 34. Of note, by using this methodology, we sample pulsed Doppler‐derived velocities in the distal LAD, which represent good correlates of coronary microvascular function (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The additive prognostic value of simultaneously evaluated CFR and wall motion abnormalities [3,[21][22][23][24], aortic distensibility indices [25], or grade of AA [26] was also demonstrated. Moreover, CFR was found to be predictive for future events in hypertensives [27], AS [6], dilated [28][29][30] and hypertrophic cardiomyopathies [5,31], in renal transplant recipients [32] and after heart transplantation [33], as well. Gender differences [24], and the prognostic value of CFR assessments on both left and right coronary arteries has also been examined [23,30].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been suggested that a "% Stress-to-Rest" EF ratio "% Stress-to-Rest" EDV ratio Fig. 3 Relationships between increasing myocardial ischaemic burden and stress-induced LV systolic and diastolic impairment multiparametric approach to simultaneously assess some of the different manifestations of the ischaemic cascade in the same stress test could offer better accuracy in detecting CAD [16,19]. Our findings demonstrate the feasibility of simultaneous evaluation of myocardial perfusion coupled with LV systolic and diastolic function in patients with suspected IHD.…”
Section: Interaction Between Cad Extent and Stress-induced LV Functiomentioning
confidence: 98%